Effects of prebiotic, probiotic and synbiotic on performance and cecal microbiome of laying hens - Tang, Shirley Gee Hoon (2016)
The rampant use of antibiotics as growth promoters in poultry feed has led to development of antibiotic resistant bacteria and accumulation of antibiotic residues in poultry eggs and meat. Probiotic bacterial strains, prebiotic oligosaccharides and their combination as synbiotics (probiotics + prebiotics) have been considered as alternatives to antibiotic growth promoters (AGPs) in poultry production. A recent study showed that prebiotic isomaltooligosaccharide (IMO) significantly improved the performance and intestinal health of broiler chickens. The effects and role of IMO however, have not been explored on laying hens. Therefore, the present study was initiated to evaluate the in vivo effects of prebiotic IMO (PRE) and probiotic PrimaLac® (PRO), administered singly, and in combination as a synbiotic (SYN) (IMO + PrimaLac®), on performance, biochemical and hematological responses, egg quality and chemical compositions of egg yolks, and diversity and functional potential of cecal microbiome of laying hens. The layer feeding trial showed that the supplementation of PRE, PRO or SYN significantly (P < 0.05) improved the body weight gain, feed intake, feed conversion ratio (FCR), egg production, egg weight, egg mass and egg size of laying hens at 20-36, 37-52 and/or 20-52 weeks of age. PRE, PRO or SYN supplementation also significantly (P < 0.05) lowered the levels of serum total cholesterol, low-density-lipoprotein (LDL) cholesterol, alkaline phosphatase (ALP), alanine aminotransferase (ALT), heterophil (H) percentages and H/L ratio, and increased lymphocyte (L) percentages at 36 and 52 weeks of age. PRE, PRO or SYN supplementation resulted in significant (P < 0.05) decreases in the cholesterol (24 and 28 weeks of age) and saturated fatty acid (SFA; 28, 32 and 36 weeks of age), and increases in the unsaturated fatty acid (UFA; 28, 32 and 36 weeks of age) and polyunsaturated fatty acid (PUFA; 28 weeks of age), including linoleic and alpha-linolenic acids of eggs without affecting the egg quality (Haugh unit, relative weights of the albumen and yolk, specific gravity, shell thickness and yolk color) (20-36 weeks of age), and lipid, carotenoid and tocopherol contents of eggs (24, 28, 32 and 36 weeks of age). The quantification of the bacterial population using quantitative real-time PCR (qPCR) showed that PRE, PRO or SYN supplementation significantly (P < 0.05) increased the populations of cecal lactobacilli and bifidobacteria at 36 and 52 weeks of age, but decreased the populations of total cecal Enterobacteriaceae and Escherichia coli at 36 weeks of age. The cecal volatile fatty acids (VFA; acetic, propionic and butyric acids) and non-VFA (lactic and succinic acids) were significantly (P < 0.05) increased whilst harmful microbial enzyme activities (β-glucosidase, β-glucuronidase and urease) significantly (P < 0.05) decreased after PRE, PRO or SYN supplementation at 36 and 52 weeks of age. The 16S rRNA deep-sequencing analysis revealed that the relative abundance of cecal lactobacilli was significantly (P < 0.05) increased in all supplemented hens (PRE, PRO or SYN) at 36 and 52 weeks of age. The relative abundance of cecal bifidobacteria was also increased significantly (P < 0.05) in PRE- or SYN- supplemented hens at 36 weeks of age, and in PRE-, PRO- or SYN-supplemented hens at 52 weeks of age. At 36 weeks of age, the relative abundance of cecal Enterobacteriaceae decreased significantly (P < 0.05) after PRE, PRO or SYN supplementation. The whole metagenome shotgun sequencing analysis indicated that the microbiome of PRE-, PRO- or SYN-fed hens were predicted to have higher percentages of genes involved in carbohydrate metabolism (gluconeogenesis/glycolysis, citrate cycle, butanoate and pyruvate metabolisms); xenobiotics biodegradation and metabolisms (dioxin, xylene and toluene degradation); lipid metabolism (arachidonic acid metabolism and fatty acid elongation); Adenosine Triphosphate (ATP)-binding cassette transporters (ABC transporters); signalling molecules and interaction; immune and digestive systems as compared to control hens at 36 weeks of age. In conclusion, the results of the present study showed that the supplementation of PRE, PRO or SYN could improve the hen performance, produce eggs with lower cholesterol and SFA, and promote the hen health by altering the microbial populations, diversity and functional potential of cecal microbiome without affecting the egg quality of laying hens.